SEJARAH PERKEMBANGAN TAPAK SUCI PONPES MUALIMIN DI BANGKINANG (1997-2018) - Defri, Mhd Rizki; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Tapak Suci son of Muhamadiyah or abbreviated as Tapak Suci is a sect, college, organization, Pencak Silat who is a member IPSI (Indonesian Pencak Silat Ties). Tapak Suci was established on July 31, 1963 in Kauman, Yogyakarta. Tapak Suci has a motto with faith and my character becomes strong without faith and my character becomes weak. With the development of the Tapak Suci in the area of Riau precisely in Kampar district more specifically in the Mualimin boarding school, brought by Mr. Zukirman in 1997. The purpose of this research is to find out the history of the development of the Tapak Suci place of Islamic boarding school in Bangkinang (1997-2018). The method used in this study is a historical research method which consist of four stages, namely heuristics, verification, interpretation, and historiography. The data obtained from the result of the interviews are added to the data obtained from the books. Data obtained from the result of interviews and literature studies are then analyzed in their own language. As for location of the study conducted in Kampar district, especially in the Islamic boarding school. This research was carried out starting from the issuance of a research pemit until this thesis was completed. Data collection techniques used are observation techniques, interview techniques, library techniques, documentation techniques. The result of this study explain the development of the Tapak Suci in the Mualimin boarding school divided by three developments namely the period of father Zukirman, the period of the father of the Diad, the period of the father of Nurman. Tapak Suci at the Islamic boarding school has received many strong students called Tapak Suci cadres.Key Words: Tapak Suci, One Of The Names Of Pencak Silat